PCR-based chromosome walking: the SFR 3 case - Amid, Azura; Warren, Garreth J.; Bramley, Peter M. (Asian Network for Scientific Information, 2006)
In this study, mapping experiments were initiated in a region of 34.23 cM or 2.7 Mb to map the SFR3 gene into the smallest possible region on chromosome I. Eleven new PCR markers had been designed to fine map the gene. Roughly 557 F2 plants tested in these experiments and 38 lines were then used in the fine mapping experiments. The fine mapping experiments left the SFR3 region amongst 26 genes. Finally, 13 pseudogenes and transposable elements were eliminated and this left the SFR3 gene region amongst 13 genes in a 0.19 Mb region, which is represented by 4 BAC clones. The PCR-based chromosome mapping experiments to fine map the SFR3 gene have successfully decreased the SFR3 region from 2.7 to 0.19 Mb. We concluded that PCR-based chromosome walking is a convenient method to clone SFR3 gene.